2010
DOI: 10.1111/j.1550-7408.2010.00500.x
|View full text |Cite|
|
Sign up to set email alerts
|

Redescription of Favella ehrenbergii (Claparède and Lachmann, 1858) Jörgensen, 1924 (Ciliophora: Choreotrichia), with Phylogenetic Analyses Based on Small Subunit rRNA Gene Sequences

Abstract: The identification of Favella ehrenbergii, a marine planktonic ciliate, has largely been based on its lorica features. This approach is potentially problematic given the polymorphic lorica during this organism's life cycle. We isolated a population of F. ehrenbergii from the coastal waters of Incheon, Korea, and revealed its infraciliature using the protargol staining method. Phylogenetic analysis based on small subunit rRNA gene sequences was also performed. Results showed that this population possessed 16 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 20 publications
2
41
1
Order By: Relevance
“…The evolution in the majority of freshwater tintinnids with the two de novo‐originating ventral organelles was described in detail by Agatha and Strüder‐Kypke (), while new data on Favella ehrenbergii (Claparède and Lachmann, ) Jörgensen, provided by Kim S. Y. et al. (), F. panamensis (this study), and F. arcuata (this study) necessitate an update of the evolutionary hypothesis on tintinnids with a ventral kinety. In these tintinnids, the dikinetids of the right and left ciliary fields, except for the anteriormost ones, transformed into ciliated monokinetids, producing the pattern of Nolaclusilis Snyder and Brownlee, (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…The evolution in the majority of freshwater tintinnids with the two de novo‐originating ventral organelles was described in detail by Agatha and Strüder‐Kypke (), while new data on Favella ehrenbergii (Claparède and Lachmann, ) Jörgensen, provided by Kim S. Y. et al. (), F. panamensis (this study), and F. arcuata (this study) necessitate an update of the evolutionary hypothesis on tintinnids with a ventral kinety. In these tintinnids, the dikinetids of the right and left ciliary fields, except for the anteriormost ones, transformed into ciliated monokinetids, producing the pattern of Nolaclusilis Snyder and Brownlee, (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Comparison of the ciliate host sequences to GenBank sequences by the use of BLASTn often yielded very close matches, although an exact identity between novel and GenBank sequences was found only in the case of Favella ehrenbergii and F. panamensis (AY143572), which may be synonymous (26). In other cases, such as that of E. pectinis, very similar sequences (4 base differences across 1,685 sites) attributed to the same species were found in GenBank.…”
Section: Host Morphometrymentioning
confidence: 87%
“…This result implies that there are many cryptic species within the Tintinnida, just as with other planktonic taxa such as diatoms (Amato et al 2007), copepods (Chen & Hare 2008) and aloricate ciliates (Katz et al 2005). On the one hand, studies with laboratory cultures of tintinnid species have shown that size and morphology of the lorica can vary greatly even within a single species (Gold 1968, 1973, Kim et al 2010). On the other hand, the present study showed that even if there are no notable differences in the size and shape of the loricae between tintinnids, they do not necessarily share the same descendant and thus the same genealogical position.…”
Section: Discussionmentioning
confidence: 99%
“…According to the nuclear SSrRNA phylogeny, specimens of F. ehrenbergii from Korea were close to F. panamensis Kofoid & Campbell and F. campanula, while specimens of F. ehrenbergii from eastern North America were close to F. taraikaensis (from northern China) and Metacylis sp. Since lorica morphology is very similar between F. ehrenbergii and F. taraikaensis, Kim et al (2010) suggested that Snoeyenbos-West et al (2002) might have misidentified their species. However, both specimens of F. ehrenbergii and F. taraikaensis from Sendai Bay were found not only in clade A but also in clade B, and formed subclades within each clade with other morphospecies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation